THE CONTRIBUTIONS ON THE STUDENT’S WAY OF LEARNING TOWARDS STUDY RESULT ON BUILDING MATERIALS TRAINING EDUCATION CLASS X, CONSTRUCTION ENGINEERING MAYOR AT PADANG VOCATIONAL HIGH SCHOOL 1 - 1947-1964 , Eldiansyah Putra (Universitas Negeri Padang, 2016)
The problem in this research is the bad way of student’s way of learning, it proves by the unprepared condition of student’s in the building material lesson, and almost 40% of the student’s score is below the completeness standard criteria (CSC). This research is aimed to express how big the contributions on the student’s way of learning toward the study result on building materials training education class X, construction engineering mayor at Padang Vocational High School 1. The research hypothesisis that there is a contributionon The Student’s Way of Learning Towards The Study Result on Building Materials Training Education Class X, Construction Engineering Mayor At Padang Vocational High School 1. The population in this research is all of the students in construction engineering mayor that studied about construction materials training education that consist of 66 students. Sample taking technique is a total sampling with the sample amount 66 students.Data type that had been using is a primary and secondary data. Primary data was obtained by distributing the questionnaire about studying method to the students, while secondary data is a learning result in a form of scores of Construction Materials Lesson by the students. Analysis technique data that had been used are: (1) Descriptive Analysis, (2) Analysis condition testing, that consist of normality testing and linearity testing to prove that data distributions based on samples that distributed normally and linearly, and (3) hypotheses testing.Analysis result shows that the way of learning contributes 60.9% toward the study result of Class X Construction Engineering Mayor, Padang Vocational High School 1. This thing can be seen from score Sig (2-tailed) 0.000<Alpha (0.05). Based on that testing, it means that there is a positive connection between student’s way of learning Towards Study Result on Building Materials Training Education Class X, Construction Engineering Mayor At Padang Vocational High School 1. Keywords: Contributions, Way of Learning, Learning Result